(untitled) (Szociológiai Szemle, 2024)
The transition from a planned to a market economy had hardly begun in Hungary when sociologists and other social scientists sensitive to social ills began to voice their fears of and hopes for the effects of the economic transformation. A number of more or less amorphous or malleable new phrases have cropped up both in the jargon of sociological discourse and in common speech, all denoting supposed or real social problems. In the course of this paper I will discuss some of these.